POLA ASUH ORANG TUA PADA ANAK TUNARUNGU YANG BERPRESTASI DI BIDANG OLAHRAGA - Putri, Adinda Meita (2016)
Pendidikan pertama yang diperoleh anak tunarungu adalah pendidikan didalam keluarga. Orang tua berperan sebagai pendidik yang tentunya memiliki aturan tersendiri dalam menerapkan pendidikan kepada anaknya berdasarkan pola asuh yang digunakan. Pola asuh yang diterapkan orang tua sangat berpengaruh pada tumbuh kembang anak tunarunguserta menjadi salah satu faktor anak tersebut dalam meraih prestasi. Anak tunarungu memiliki hambatan yang akan mempengaruhi segala aspek kemampuan hidupnya juga ternyata mampu berprestasi dan tidak kalah dengan anak mendengar. Penelitian ini bertujuan menggambarkan bagaimana pola asuh yang diterapkan orang tua pada anak tunarungu yang berprestasi di bidang olahraga. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode deskriptif. Subjeknya adalah para orang tua dari ketiga siswa/i berprestasi di SLB X. Hasil penelitian ini menunjukan aspek tuntutan (demandingness) terhadap anak, penerimaan (accepting) pendapat anak, dan respon (responsiveness) pada prestasi anakyang mengacu pola asuh demokratis serta controlling kedisiplinan anak yang mengacu pola asuh otoriter akan baik diterapkan kepada anak tunarungu terutama pada proses anak meraih prestasi sebagaimana ketiga siswa/i tersebut. Pola asuh yang digunakan orang tua RA lebih cenderung demokratis- otoriter, dimana menerapkan demandingness yang rendah namun dengan controlling, accepting, dan responsiveness yang tinggi. Subjek kedua yaitu orang tua SDJ lebih cenderung pada pola asuh otoriter-demokratis, dimana menerapkandemandingness, controlling, accepting, dan responsiveness yang tinggi kepada anak. Subjek terakhir yaitu orang tua ECS lebih cenderung pada pola asuh permisif-demokratis, dimana demandingness, controlling, dan responsiveness rendah namun memiliki accepting yang tinggi. ; The first education obtained by a hearing impaired child is an informal education inside his/her family where the parents hold an important role on it. Parents play part as a mentor as well as an educator which certainly has rules or a specific guidelines in terms of teaching their child based on their applied parenting patterns. The type of parenting which applied inside the family is highly affecting on the deaf children's development, and also become one of the major factors for them to reach their achievement. Hearing impaired children possess a specific obstacle which constantly influence their live aspects are yet still able to success and up to par with the normal ones. The purpose of this research is to determine the parenting style which has been applied to the high-schieved deaf children. The approach being used in this research is by a qualitative approach with a descriptive method. The research subjects are the parents from 3 different high achieving students at SLB X. This research shows that these demandingness (parents expectations/desires to the children), accepting (parents acceptance of children opinions) and responsiveness (parents response to children's achievements) which are referring to a democratic parenting, combined with a controlling (parents discipline control for the children) aspect based on an authoritarian style, are the most suitable parenting pattern to be applied on and highly affecting for hearing impaired children development, especially in terms of supporting the children process to reach achievement as shown from those 3 different high achieved students.The parenting style which applied by RA's parents is more democratize-authoritarian, where implementing a low demandingness but with a higher degree of controlling, accepting and responsiveness. The second subject, SDJ's parents, are fall into the type of authority-democratic, shown by implementing a high practice on every aspects mention above. The last subject, which is ESC's parent, is classified as permissive-democratic, where several aspects such as: demandingness, controlling, and responsiveness are considered low, yet focusing on a high accepting aspect.